Le lean et l’activité humaine - Fabrice Bourgeois; Olivier Gonon (Activités)
Lean production and human work. How should ergonomics react to this new concept of efficiency ? Ergonomists are receiving a growing number of requests directly connected with Lean production. It’s true that there’s nothing really new about just in time methods, kanban, kaisen and so on in the business environment. What is new is the way Lean has burst into the company as a global system, and the uproar caused by the values it encompasses. This points to a major change in the notional referents of companies’ efficiency, impacting work resources and the interpretation of results. The promises of Lean offer companies an opportunity to « change », not just for the « better » (greater agility and flexibility, and faster reaction times) but also for the « good » (emancipation from Taylorism to the point of finding a natural closeness to ergonomics). That last statement raises a number of questions. It was introduced by Lean specialists rather than by ergonomists, and it seems natural therefore that a « disciplinary » response, which does not yet exist, should be provided. There are already several different positions in the field of ergonomics but they cover a very broad spectrum, ranging from those who claim that the Lean is practically equivalent to the end of ergonomics, thereby supporting the correspondence theory, to those who see it as a new form of Taylorism, a new threat to be fought against. On this topical and controversial issue, the authors’ intention is to initiate a dialogue between practitioners and researchers to reach a better understanding of the relative positions of work and of ergonomics.